2019
DOI: 10.1111/jfpe.13176
|View full text |Cite
|
Sign up to set email alerts
|

Determination of drying kinetics, some physical, and antioxidant properties of papaya seeds undergoing microwave vacuum drying

Abstract: The effects of microwave power (MP, 100–600 W) on the drying kinetics, as well as the physical and antioxidant properties of papaya seeds dried under microwave vacuum drying (MVD) were investigated. The results found that moisture diffusivity increased in the order of 10−8 with an increase in MP. Shrinkage increased from 1.2 to 4.9% and bulk density decreased from 3,441 to 1,091 kg/m3, respectively, while the moisture content decreased. The antioxidant contents of all of the MVD samples were higher than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 43 publications
(65 reference statements)
2
12
0
Order By: Relevance
“…Microwave drying papaya seeds at 600 W increased the oil extracts Trolox equivalent antioxidant capacity (TEAC) by 17 %, while microwave drying at 100 W decreased TEAC by 8 % ( Bualuang et al., 2018 ). The findings showed that an increase in the microwave power enhanced the oil extracts antioxidant activity.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
See 1 more Smart Citation
“…Microwave drying papaya seeds at 600 W increased the oil extracts Trolox equivalent antioxidant capacity (TEAC) by 17 %, while microwave drying at 100 W decreased TEAC by 8 % ( Bualuang et al., 2018 ). The findings showed that an increase in the microwave power enhanced the oil extracts antioxidant activity.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
“…Preservation and maximization of these bioactive phytochemicals during seeds drying should be prioritized. Bualuang et al (2018) evaluated the effect of microwave vacuum drying (100 mbar, 100, 300, 450 and 600 W) papaya seeds and found out that total phenolic content significantly improved by 11 %, but decreased by 16 and 20 % when the microwave power was increased from 100 to 300, 450 and 600 W, respectively. In a related study, Al reported a significant effect of oven drying (60, 70 and 80 C for 24 h) kinnow marandin, orlendo orange and eureka lemon seeds on the phenolic compounds of the extracted oil.…”
Section: Tocopherols Phytosterols and Polyphenolsmentioning
confidence: 99%
“…i. MWVD was performed using a microwave oven (Samsung MS23F301E) connected to a vacuum pump (New IM-TECH IM125D) with a pumping rate of 0.108 m 3 /min (Bualuang et al, 2019). Then, 100 g of A. ilicifolius leaves were placed into the vacuum container, and into the oven cavity.…”
Section: Drying Methodsmentioning
confidence: 99%
“…This thus causes a reduction in the retention of phytochemical compounds in the dried products (Onwude et al, 2016). Furthermore, in comparison to hot air convective drying, both microwave and microwave-vacuum drying can reduce the drying times while maintaining the product quality (Hamrouni-Sellami et al, 2013;Bualuang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Among other factors, the differences observed could be due to variation in cultivar, seed drying method, oil extraction technique, and fruit growing region. Nonetheless, the TPC results were lower than those from other fruit seed oil such as papaya (10.66-13.29 mgGAE/g oil) and avocado (25.72-70.19 mgGAE/g oil) [31,32]. The DPPH assay has been used widely to evaluate the antiradical activity of plant extracts, including seed oil.…”
Section: Total Phenolic Content and Antiradical Activitymentioning
confidence: 99%